Biomphalaria glabrata (Say, 1818) como hospedeiro paratênico de Angiostrongylus vasorum (Baillet,1866) Kamensky, 1905 - Isabela Resende Ávila (2019)
Angiostrongylus vasorum is a nematode whose adult forms can be found in the pulmonary arteries and right heart of domestic dogs and wild canids, which are the definitive hosts. In addition to the importance in the small animal clinic, this parasite is discussed in terms of public health due to the possibility of human infection. The heteroxene cycle presents several molluscan species as intermediate hosts, which are infected by ingestion and / or penetration of first stage larvae of the parasite. In the molluscs two seedlings of first instar larvae (L1), L2 and L3 occur, which is infective to the definitive hosts. In addition to these infection routes, there may also be paratenic hosts, which may harbor L3, such as frogs, lizards, mice, rats and birds. Considering that several issues inherent to the cycle of this parasite still remain obscure, the present study aimed to evaluate if Biomphalaria glabrata can be paratenic host of Angiostrongylus vasorum, identifying the possible routes of penetration of these larvae, the migratory route, besides describing the possible changes at different times of infection. Third instar larvae were recovered from B. glabrata molluscs 30 days after infection with 1.000 L1 of A. vasorum using the modified Baermann method. The recovered L3 were used for infection of mollusks of the species B. glabrata, with the inoculum of 100 L3 + (larva of third stage coming from mollusc infected with 100 L3). Third-instar larvae of A. vasorum were recovered alive and active in the mollusc's tissues, thus demonstrating their permissiveness to L3 + infection. The other specimens of infected molluscs were fixed in 10% formaldehyde for histological evaluation, where the presence of larvae in the tissue was observed and they tended to remain in the cephalopodal region. Regarding the viability of L3 +, further studies are still needed, since two mixed breed dogs were submitted to canine pate with the presence of L3 + and so far only four L1 were found in the feces of the dogs. This work demonstrates, for the first time, the possibility of B. glabrata to participate as paratenic host in the A. vasorum cycle.